(untitled) (American Journal of Islam and Society, 2007)
In the face of modernity and its erosion of traditional values, we need to preserve something of the wisdom of traditional culture. The traditional cultures have taken thousands of years to evolve and are necessary to preserve. They are the carriers of the accumulated wisdom of the people since Antiquity. They give man a sense of belonging, acceptance, and assurance. They enshrine the values, which define meaning, guide, motivate, and lead people to fulfillment. We find cultural traditions still alive in the rural communities of Southeast Asia. It is to these communities that we need to turn to guide us on our road to the future ...